Exploring the Impact of Evolving Consumer Behavior on Purchase Intention in Social Commerce Environments - Budianto, Philip Antonius; Halim, Erwin; Setiawan, Ariiq Naufal Arrafi; Effendi, Hafizd Rasya (Universitas Amikom Purwokerto, 2025)
This Preliminary study explores the influence of evolving consumer behavior on purchase intention in the context of social commerce. In the contemporary landscape, where the convergence of social media and online shopping has become pervasive, a comprehensive understanding of the pivotal factors that influence purchasing decisions has become imperative. The research study will examine five primary variables: social media marketing content, consumer behavior change, consumer engagement, data security, and conversion rate. The findings indicate that marketing content, behavior change, data security, and conversion rate have a substantial impact on the growth of social commerce and purchase intention. However, consumer engagement does not demonstrate a significant effect. The data were collected from 50 respondents, and the survey was initiated in March 2025. Most of the participants are women (57.5%) and between the ages of 12 and 27 years (97.1%), which suggests that young consumers are actively involved. Most people live in Jakarta and the surrounding cities. Most of them have a diploma or a bachelor's degree, and 57% are currently studying. These statistics highlight the significant presence of young, educated people in the world of social commerce. The study gives businesses ideas to improve their strategies. These ideas include creating interesting content, building trust, and adapting to new consumer behaviors.